Do colour-morphs of an amphidromous goby represent different species? Taxonomy of Lentipes (Gobiiformes) from Japan and Palawan, Philippines, with phylogenomic approaches. Issue 8 (17th November 2021) - Maeda, Ken; Kobayashi, Hirozumi; Palla, Herminie P.; Shinzato, Chuya; Koyanagi, Ryo; Montenegro, Javier; Nagano, Atsushi J.; Saeki, Toshifumi; Kunishima, Taiga; Mukai, Takahiko; Tachihara, Katsunori; Laudet, Vincent; et al.
Abstract : We document four male colour morphs of the Indo-Pacific goby genus Lentipes in Japan and the Philippines. Despite distinctive colour patterns, males of the different morphs could not be distinguished by meristic or morphometric characters. In contrast, co-occurring females had very similar colouration and could not be sorted into different types. We observed that the four types are not distinguished by mitochondrial genome sequences. On the other hand, genome-wide SNPs analysis clearly separated the four types, suggesting that they indeed represent four independent lineages. We considered that the four lineages could have diverged recently, and therefore, the sorting of mitochondrial haplotypes may not have been completed yet. One of the four lineages is identified as L. armatus Sakai & Nakamura, 1979, and the other three are described in this study as new species: L. kijimuna sp. nov., L. bunagaya sp. nov., and L. palawanirufus sp. nov. We observed that males display their species-specific body colourations during courtship. Pre-zygotic isolation due to female preferences for different male body colours is probably the primary mechanism of reproductive isolation between the four species. http://zoobank.org/urn:lsid:zoobank.org:pub:95C19A65-8907-48F6-AA0B-2ACF711C0297